Torsional deformation and rotary driving characteristics of SMA thin strip (Archives of Mechanics - Test, 2009)
The torsional deformation properties of a TiNi shape-memory alloy thin strip were investigated. The results obtained are summarized as follows. (1) The martensitic transformation starts at the edge of the thin strip. (2) The torsional deformation properties change slightly under thermomechanical cycling. (3) The fatigue life in pulsating torsion is longer than that in alternating torsion. (4) A simple rotary driving element can be developed by using the SMA thin strip.